O atendimento educacional especializado como rede de serviços e apoio na educação: contribuições da teoria histórico-cultural - Antunes, Clarice Filipin de Castro (2015)
This research aimed to study the institutionalization of Educational Service Specialist - ESA in order to understand the contributions of this service to the process of education of the target group of special education students enrolled in regular education. To this end, a study was conducted of documentary and bibliographical. In desk research we prioritize both federal, and state and municipal, dealing specifically with ESA; since the national guidelines for Special Education in inclusive education perspective establishing a change in the schooling situation of the target group students in this type of education, and directs all educational systems to make available the services themselves of this service in the regular network. The bibliographic part supported the study on the understanding of the educational work to be done in ESA, with an emphasis on investigation of cognitive processes of students with disabilities. The mechanisms and strategies were selected and the resources to be used by means of educational practices and teacher training to work in this type of education. The research is oriented in the Historic-Cultural Psychology, this reference that in the case of Special Education, it is relevant in order to design for it defended disabled person as someone who should be seen and treated beyond its limitations; be attentive to the limitation that disability can not impose, but the possibilities that may arise. Thus, based on the study conducted, we can say that there are serious difficulties as regards the realization of the ESA, both the enrollment process, but also in the humanization of these subjects. Among many factors that have contributed to this situation, one of them lies related to the interests of capitalist society and, as the school has arranged to meet this system. As a result of investigation, whose epistemological assumptions of this work are conspicuous by humanization of all subjects, it is observed that the school routine, in the execution of educational practice have become even partially. The documentary aspect we noted that the legislation focuses the prerogative of what the practice in its entirety, when considering the context of the current system has not guaranteed. Thus, we conclude that the enforcement of the ESA should be given attention and prepositions in the performance of the special education teachers, both in terms of legislation and in their practice.